1994
DOI: 10.1177/095632029400500205
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Pathways of the Mono- and Bis(Pivaloyloxymethyl) Esters of Azidothymidine 5′-Monophosphate in Cell Extract and in Tissue Culture Medium: An Application of the ‘on-line ISRP-Cleaning’ HPLC Technique

Abstract: Bis(pivaloyloxymethyl) azidothymidine 5'-monophosphate (piv 2-AZTMP) was designed as a cell membrane-permeable precursor of AZTMP. We have reported previously that when incubated with CEM cells deficient in thymidine kinase, piv 2-AZTMP gives rise to intracellular AZTMP and the corresponding diphosphate (AZTDP) and triphosphate (AZTTP). Under similar conditions, no intracellular nucleotides were formed with AZT. However, the mechanism bỹ ich piv 2-AZTMP is converted to AZTMP has not been established. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 26 publications
3
32
1
Order By: Relevance
“…Consequently, a mononucleoside phosphotriester derivative of AZT cannot exhibit a higher in-vitro anti-HIV activity than that of AZT in cells in which the cytosolic thymidine kinase activity is expressed such as PHA-stimulated PBMCs, thereby explaining the similar inhibiting capacity of the bis(MeSATE) ester 1 and the bis(POM) ester 3 derivatives as AZT in PBMCs. The slight decrease in anti-HIV-1 activity observed with these two pronuc1eotides may be related to a faster intracellular accumulation of AZTMP by the parent drug (Pompon et al, 1994;Lefebvre et al, 1995). It was demonstrated that an accumulation of this metabolite causes a potent inhibition of thymidylate kinase resulting in a blockage of the subsequent phosphorylation to 3'-azido-2',3'-deoxythymidine 5'-diphosphate (AZTOP) (Furman et al, 1986;Harrington et el., 1987;Frick et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a mononucleoside phosphotriester derivative of AZT cannot exhibit a higher in-vitro anti-HIV activity than that of AZT in cells in which the cytosolic thymidine kinase activity is expressed such as PHA-stimulated PBMCs, thereby explaining the similar inhibiting capacity of the bis(MeSATE) ester 1 and the bis(POM) ester 3 derivatives as AZT in PBMCs. The slight decrease in anti-HIV-1 activity observed with these two pronuc1eotides may be related to a faster intracellular accumulation of AZTMP by the parent drug (Pompon et al, 1994;Lefebvre et al, 1995). It was demonstrated that an accumulation of this metabolite causes a potent inhibition of thymidylate kinase resulting in a blockage of the subsequent phosphorylation to 3'-azido-2',3'-deoxythymidine 5'-diphosphate (AZTOP) (Furman et al, 1986;Harrington et el., 1987;Frick et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…) involved, in the first step, an enzyme-mediated activation process leading to new phosphotriesters which were chemically unstable and which decompose spontaneously to afford the phosphodiester intermediates. In the second step, these phosphodiesters will then be converted into AZTMP following a similar mechanism and/or by action of phosphodiesterases (Puech et el., 1993;Pompon et al, 1994;Lefebvre et el., 1995). The hydrolysis of the pronucleotides 1-3 result in the formation of the 5'-mononucleotide and also small organic molecules as byproducts (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT-2 cell extract was prepared from MT-2 cells according to a previously published procedure (21). Extract (80 l) was transferred into a screw-cap centrifuge tube and incubated at 37°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of a relatively poor conversion rate by the activating enzyme other than ABC are stavudine (d4T) by thymidine kinase (TK) [7,8], zalcitabine (ddC) by 2 0 -deoxycytidine kinase [9,10], and didanosine (ddI) by 5 0 -nucleotidase [4,5]. Therefore, several attempts have been undertaken to deliver activated (phosphorylated) nucleoside analogues directly into the virusinfected target cells [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. One of these approaches has proven very successful when applied on thymidine analogues such as d4T.…”
Section: Introductionmentioning
confidence: 99%